Neighborhood effect of geographical distribution of urban facilities on older adults' participation in hobby and sports groups. (December 2022) - Kim, Hongjik; Hino, Kimihiro; Asami, Yasushi; Kondo, Naoki
Abstract: Understanding the effect of neighborhood facilities on older adults' participation in hobbies and sports activities can provide solid evidence for effective health promotion policies. However, few studies have considered the relationship between the geographic accessibility of neighborhood facilities and their degree of spatial clustering with changes in group participation over time. This study examined whether the geographical distribution of neighborhood facilities—their geographic accessibility and degree of spatial clustering—can facilitate older adults' group participation. Longitudinal data of 20, 151 older adults living in 339 elementary school districts were collected through the Japan Gerontological Evaluation Study. The findings within the Japanese context show that high geographic accessibility of neighborhood facilities and their spatially clustered patterns are related to an increase in group participation. Meanwhile, for older adults who have close ties with neighbors, an increase in sports group participation can be negatively impacted despite the great geographic accessibility to city parks. Spatially dispersed eating facilities are also related to good relationships with neighbors, facilitating participation in sports groups. Therefore, policymakers should carefully consider the various dynamics in the effect when discussing the choice of facility location to facilitate older adults' participation in hobbies and sports groups. Highlights: Accessibility of facilities and their clustering degree is considered. Accessibility of parks shows the greatest direct effect on group participation. Accessibility of parks shows a negative indirect effect on sports participation. Clustered eating places and food stores increase group participation. Dispersed eating places also increase participation in sports groups.